Implementation Of Scientific Writing Programs In Improving The Literacy Of Sixth-Grade Students At Pondok Modern Darussalam Gontor Ponorogo - Ahmad Hilmi Al-Mujtahidi; Muhammad Fathi Mubin; Nurul Aziziah; Ihwan Mahmudi; Febriko Faiz Mahendra (CV Putra Publisher, 2026)
This study aims to analyse the implementation of a scientific writing program in improving the literacy of sixth-grade students at Pondok Modern Darussalam Gontor. Literacy development has become an important aspect of 21st-century education, including in Islamic boarding schools, where students are expected to develop academic and critical thinking skills through structured educational programs. This study employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving sixth-grade students, teachers, and supervisors participating in the scientific writing program. Data were analysed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the scientific writing program contributes positively to students’ academic literacy development. The program enhances reading comprehension, idea development, academic writing skills, and critical thinking abilities. In addition, students demonstrated greater participation in academic activities, including discussions, presentations, and scientific reporting. The study also found that systematic guidance, intensive supervision, and structured writing stages play significant roles in fostering a sustainable literacy culture within the pesantren environment. This study concludes that the scientific writing program is an effective strategy for strengthening academic literacy among students in Islamic boarding schools. The findings provide practical insights for the development of literacy-based educational programs in pesantren and other Islamic educational institutions.